Analisis Putusan Hakim Pengadilan Agama Surakarta Pada Perkara Ekonomi Syariah (Studi Putusan Nomor 432/Pdt.G/2023/PA.Ska) - Bataweya, Ardin; Muhammad Fuad, Andi (Al-Mizan (e-Journal), 2024)
This study analyses the results of the decision by the judge of the Religious Court with Case Number: 432/Pdt.G/2023/PA.Ska. This research is a case study analysed with a normative juridical approach. The results showed that the Surakarta Religious Court granted the customer's lawsuit on the grounds of unlawful acts committed by the Sharia Rural Bank of Dana Mulia, namely withholding savings money without clear reasons. Although the defendant filed an exception, the judge rejected it and upheld the defendant's guilt, with both parties sentenced to pay court costs. The judge's decision emphasised that the clause of the agreement between the bank and the customer was a valid basis, so the judge rejected the defendant's exception with the argument that the elements of tort were not fulfilled in the case. This conclusion was supported by legal considerations, including disqualification in person, the judge's assessment of the elements of tort, and the application of Indonesian laws and regulations. This decision has a significant impact on both parties in the settlement of sharia economic case Number 432/Pdt.G/2023/PA.Ska. at the Surakarta Religious Court.